2018
DOI: 10.16984/saufenbilder.383770
|View full text |Cite
|
Sign up to set email alerts
|

KOROVKIN THEOREM VIA STATISTICAL e-MODULAR CONVERGENCE OF DOUBLE SEQUENCES

Abstract: The main purpose of the present paper is to obtain an abstract version of the Korovkin type theorem via the concept of statistical e-convergence in modular spaces for double sequences of positive linear operators. After proving this theorem, we give an application showing that the new result is stronger than classical ones. Also, we study an extension to non-positive operators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…Figure 5 shows the electronic transitions in Yb 3+ , Gd 3+ and Er 3+ ions, but they have not been observed in the ZrO 2 :Dy 3+ phosphor. However, the emission intensity of Gd 3+ co-doped samples increased while the emission intensities of Yb 3+ and Er 3+ co-doped Dy 3+ phosphor have been reported in our earlier article [71].…”
Section: Results Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Figure 5 shows the electronic transitions in Yb 3+ , Gd 3+ and Er 3+ ions, but they have not been observed in the ZrO 2 :Dy 3+ phosphor. However, the emission intensity of Gd 3+ co-doped samples increased while the emission intensities of Yb 3+ and Er 3+ co-doped Dy 3+ phosphor have been reported in our earlier article [71].…”
Section: Results Discussionsupporting
confidence: 45%
“…For instance, Arsenev et al [42] reported that ZrO 2 single crystals doped by difference in the number of the luminescence centre. We argued that the rare-earth dopants [71,81,82] increase oxygen vacancies [83] and thus the number of luminescence centres rises [42,77,[84][85][86].…”
Section: Discussionmentioning
confidence: 99%